2015
DOI: 10.1016/j.ypmed.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in physical activity patterns among older adults who fall

Abstract: Objective This study describes gender differences in the level and pattern of physical activity in groups of older adults who were frequent fallers, intermittent fallers, or non-fallers. Methods Interviews were conducted with adults aged 50 years and older (N = 1834) at senior centers across Pennsylvania from 2010 to 2011. Self-reported falls and validated measures of physical activity were collected at baseline and at 6- and 12-month follow-up assessments. Results Complete follow-up data were available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Subjects with 60 years and above have up to three times higher chance of falling when compared to middleaged adults [39]. The larger proportion of female fallers observed in the present study was also previously described [40] and might be related to several factors, such as hormonal differences, lower muscle function, and differences in physical activity patterns among women [41].…”
Section: Discussionsupporting
confidence: 79%
“…Subjects with 60 years and above have up to three times higher chance of falling when compared to middleaged adults [39]. The larger proportion of female fallers observed in the present study was also previously described [40] and might be related to several factors, such as hormonal differences, lower muscle function, and differences in physical activity patterns among women [41].…”
Section: Discussionsupporting
confidence: 79%
“…Declines during emerging adulthood may be driven by psychosocial factors, including life transitions (e.g., completion of mandatory schooling and full time work 7,8 ), and declines at older ages are driven be chronic disease morbidity 11 and environmental factors related to safety and accessibility 16 . These effects may also vary by sex during childhood and adolescence due to differences in motivation, interests 17 , and access to sports participation 18 ; and, during later life due to differences in chronic disease prevalence 19 , frailty 20 , and fall risk 21 .…”
Section: Introductionmentioning
confidence: 99%
“…J. Jefferis et al, 2015; Lobo, 2012; Mertz et al, 2010; Peeters et al, 2010; Stahl & Albert, 2015; Wijlhuizen, Chorus, & Hopman-Rock, 2008). Physical activity incorporates a wide range of activities including lifestyle activities (walking, housework, gardening, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the majority of our participants were regularly physically active by completing light housework and walking. A study of 1,487 older adults, 50 years of age and older, found that individuals with the highest rates of walking and household activities were frequent fallers (Stahl & Albert, 2015). The high rates of walking and light housework may explain why 40% of our participants had a fall over the 6-year study period.…”
Section: Discussionmentioning
confidence: 99%